2019
DOI: 10.17011/ht/urn.201911265022
|View full text |Cite
|
Sign up to set email alerts
|

EVE Online is not for Everyone: Exceptionalism in Online Gaming Cultures

Abstract: EVE Online is a space-themed massively multiplayer online game that has developed a reputation for being difficult and unwelcoming to new players. In this article, I explore how an emphasis on exceptionalism is present throughout discussions about EVE by its developer, the enthusiast gaming press, and survey responses of current players (N = 647). Taken together, information from these sources reinforces a public perception that EVE is a game that is of interest only to a very specific kind of player. In turn,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…are not against the terms of service and indeed are a regular part of the gameplay. This makes up a large portion of coverage about EVE by the gaming enthusiast press (Bergstrom, 2019e), but also informed the early scholarship about this game (Blodgett, 2009;Craft, 2007;White, 2008). The second generation of EVE scholarship took a more balanced approach to the game that were less focused on the outright anti-social elements of gameplay (Carter et al, 2016;Chia, 2018;Goodfellow, 2015;Milik, 2017;Warmelink, 2014;Webber & Milik, 2018).…”
Section: Eve Onlinementioning
confidence: 87%
“…are not against the terms of service and indeed are a regular part of the gameplay. This makes up a large portion of coverage about EVE by the gaming enthusiast press (Bergstrom, 2019e), but also informed the early scholarship about this game (Blodgett, 2009;Craft, 2007;White, 2008). The second generation of EVE scholarship took a more balanced approach to the game that were less focused on the outright anti-social elements of gameplay (Carter et al, 2016;Chia, 2018;Goodfellow, 2015;Milik, 2017;Warmelink, 2014;Webber & Milik, 2018).…”
Section: Eve Onlinementioning
confidence: 87%
“…Rather than being equally open to all, game scholars-especially those informed by feminist theory-have documented the ways that some demographics have an easier time entering into particular gaming communities than others [9,13,26]. Indeed, researchers have endeavored to understand the gatekeeping practiced by certain members of online communities which act as a subtle and sometimes overt judgment about who "belongs" in a particular community and who is seen as an outsider [5,18,41]. At the other end of the player lifecycle-which we note is still a nascent area of investigation-other researchers have begun to probe players experiences about quitting gaming, or never begin playing in the first place [1,4,11,21,32].…”
Section: Literature About Quittingmentioning
confidence: 99%
“…[30:11] While we recognize that the magic circle is a contested concept within the broad field of game studies [16], Dutton's provocation that the person who withdraws from a game may speak more readily about the taken for granted norms and expectations of a particular community is still useful. Indeed, in our previous work we have found that former players are candid about the barriers and hostility preventing full participation in a particular gameworld, while current players tend to be focused on maintaining the exclusivity and mystique associated with the same game [3,5]. Despite the insights they offer, former players are often a missing perspective in the study of the social aspects of digital gameplay, in large part due to the difficulty of identifying them during the recruitment stage of the research process.…”
Section: Introductionmentioning
confidence: 99%